MC-CUNE ALBRIGHT SYNDROME AND PRE-PUBERTAL SPONTANEOUS IMPROVEMENT IN FRACTURE RISK: A CASE REPORT - S, Lim; L, Deviga; S, Norlela; K, Nor Azmi (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Mc-Cune Albright Syndrome (MAS) is a rare disorder characterized by skeletal lesions, skin hyperpigmentation and hyperfunctioning endocrinopathies. We report a case of MAS with polyostotic fibrous dysplasia (FD) and highlight the natural history where the incidence of fracture starts to dwindle down once they reach adolescence. RESULTS A 34 year-old male presented with multiple spontaneous long limb fractures since the age of 2 years old. In addition, he has multiple café au lait spots and endocrinopathies namely, hyperthyroidism and normocalcemic hyperparathyroidism which was complicated by bilateral nephrolithiasis. The hyperthyroidism was treated with radioiodine which rendered him hypothyroid requiring thyroxine replacement. For his hyperparathyroidism, he refused any surgical intervention. With regard to his polyostotic FD, he had a total of 19 fractures over a 9-year period from the age of 2 to 11 years old. Subsequently, his fracture rate reduced markedly occurring 1to 2 times every 6 years. At the age of 15 to 17 years, he received multiple cycles of IV bisphosphonate. Thereafter, he only required intermittent IV bisphosphonates. His last fracture was at the age of 24 years old. At present, he is on a yearly IV zoledronic acid therapy. As he refuses parathyroid surgery, the plan is to give him cinacalcet in order to control his hyperparathyroidism. CONCLUSION This case illustrates vividly how the risk of fracture in MAS starts to improve markedly once affected individuals enter the second decade of life. However, the endocrinopathies associated with MAS tend to continue with the risk of new endocrinopathy occurring as they grow older.